[P113] Occupational exposure for eye, thyroid and gonads to medical workers operating in a PET/CT facility. (August 2018) - Dalianis, Konstantinos; Vlachou, Fani; Koutsouveli, Efi; Kollia, George; Prasopoulos, Vasilis
Abstract : Purpose: Personnel monitoring results provide information on routine radiation exposure, assist in work planning and allow control of the workplace. The aim of this study was to measure the gamma dose received by dedicated medical workers operating in our PET/CT department to eye, thyroid and gonads. PET/CT studies are restricted to the use of F-18 FDG, FLT and FCH are used in our center. Method: To estimate the effective dose from external exposure, all 6 members of the staff (2 nurses, 2 medical physicists, 2 technologists) had TLD badges worn at plastic glasses, on the region of gonads and in front of the thyroid area. High sensitivity thermolumiscent dosimeters were used. The measurements that were made at all stages of the PET/CT procedure: dose segmentation, injection of the radiopharmaceutical, handling the patient and positioning the patient. Results: Results show that the mean daily effective dose ( μ Sv  ±  SD) received by each member of the staff for eye were: Nurse1 13.4  ±  5, 2, Nurse2 12.19  ±  3, 2, technologist1 11.52  ±  4, technologist2 12.10  ±  2, 3, Medical Physicist1 9, 95  ±  2, 1, Medical Physicist2 8, 72  ±  3, 2. The mean daily effective dose ( μ Sv  ±  SD) received by each member of the staff for thyroid were: Nurse1 12.46  ±  4, 4, Nurse2 12.32  ±  3, 7, technologist1 11.63  ±  2, 5, technologist2 12.44  ±  2, 4, Medical Physicist1 8, 98  ±  3, 91, Medical Physicist2 8, 23  ±  2, 85. Finally the mean daily effective dose ( μ Sv  ±  SD) received by each member of the staff for gonads were: Nurse1 11.98  ±  3, 9, Nurse2 10.26  ±  2, 3, technologist1 8.26  ±  1, 6, technologist2 11.49  ±  3, Medical Physicist1 7, 65  ±  3, 6, Medical Physicist2 7, 12  ±  2, 92. Conclusions: From our results we can observe that the numbers are significantly lower than the recommended annual dose limit Daily dose to staff members Staff Eye μ Sv  ±  SD Thyroid  ±  SD Gonads  ±  SD Nurse1 13.4  ±  5, 2 12.46  ±  4, 4 11.98  ±  3, 9 Nurse 2 12.19  ±  3, 2 12.32  ±  3, 7 10.26  ±  2, 3 Technologist 1 11.52  ±  4 11.63  ±  2, 5 8.26  ±  1, 6 Technologist 2 12.10  ±  2, 3 12.44  ±  2, 4 11.49  ±  3 Medical Physicist 1 9, 95  ±  2, 1 8, 98  ±  3, 91 7, 65  ±  3, 6 Medical Physicist 2 8, 72  ±  3, 2 8, 23  ±  42, 85 7, 12  ±  2, 92 Mean Value 12.32  ±  3, 3 12.20  ±  4 10.38  ±  3, 22 Cumulative dose to staff members   Eye μ Sv  ±  SD Thyroid μ Sv ± SD Gonads μ Sv  ±  SD Cumulative dose for 100 exams 477  ±  52, 3 513.97  ±  36, 2 416.67  ±  44, 6 Dose per patient 4.78  ±  0, 52 5.14  ±  0, 36 4.17  ±  0, 45 Dose per patient per MBq 0.002 0.003 0.002